Innovation, R&D and Productivity: Evidence from Thai Manufacturing - Thanapol Srithanpong (International Journal of Economic Sciences and Applied Research, 2014)
This paper empirically examines the relationship between innovation, R&D (Research and Development), and productivity in Thai manufacturing using cross-sectional data from the 2007 Industrial Census of Thailand. We utilize a simplified structural model (CDM model) that describes the link between innovation output, R&D and productivity for the Thai case. Various estimation techniques are used to compare and provide evidence for empirical results. Our findings generally suggest that government aid and plant characteristics play an important role for a plant to engage in R&D and to be innovative, both in terms of process innovation and product innovation. Exporting plants, plants in the central region, and plants that are categorized as Head Branch type are more likely to engage in R&D and be innovative. The type of industry and specific technological characteristics of plants are shown to influence innovation effort and decisions to undertake R&D. On average, plant size, foreign ownership, exporting and product innovation are important drivers of productivity enhancement in Thai manufacturing.
Keywords: F14; L60; O31; 330; Productivity; Innovation; R&D; CDM model; Thailand